INFECTION CONTROL IN DENTISTRY: HOW TO CLEAN PHOTOGRAPHIC MIRRORS? - Marquezan, Mariana; Freitas, Amanda Osório Ayres de; Vilani, Giselle Nalback Lemes; Santiago, Rodrigo César; Costa, Luiz Felipe de Miranda; Alviano, Daniela Sales; Torres, Sandra Regina (Saúde (Santa Maria), 2013)
http://dx.doi.org/10.5902/223658345221 The aim of this study was to evaluate the efficacy of six different methods of disinfection and sterilization of intra-oral photographic mirrors through microbiological testing and to analysis their potential harm to mirrors’ surface. Fourteen occlusal mirrors were divided into seven groups. Group 1 comprised two mirrors as received from manufacturer. The other six groups comprised mirrors disinfected/sterilized by autoclave, immersion in enzymatic detergent, and friction with chlorhexidine detergent, chlorhexidine wipes, common detergent and 70% ethylic alcohol. Microbiological and quality surface analyses were performed. Sterilization in autoclave was microbiologic effective, but caused damage to the mirror surface. Chlorhexidine (in wipes or detergent) and liquid soap were effective disinfectant agents for photographic mirrors decontamination, without harmful effect on its surface. Enzymatic detergent immersion and friction with 70% ethylic alcohol were not effective as disinfectant agents for photographic mirrors decontamination. According to the results, the more effective and safe methods for photographic mirrors disinfection are friction with chlorhexidine and liquid soap.